The Effect of Periodic Maintenance on Pervious Concrete Pavements - Silva,Rodrigo Garozi da (2021)
ABSTRACT Pervious concrete pavements are interesting from an environmental and social viewpoint. However, this type of pavement has as the main disadvantage of losing permeability over time by the clogging process. The aim of this work is to evaluate the periodic cleaning efficiency of using a blower, mainly during the first four months after paving. A pervious concrete sidewalk was constructed and cleaning was carried out, monthly in one half and weekly in the other half. Infiltration rate tests, following ASTM C1701, were performed weekly at eight spots arranged symmetrically on each half of the pavement. The results showed that using a blower for periodic cleaning was efficient. Both halves, with monthly and weekly cleaning, did not present significant statistical difference in their infiltration rates. In this sense, monthly maintenance is the most suitable due to less time and fuel are spent for cleaning, collaborating as an environmental-friendly alternative. This work showed that the performance of periodic maintenance can be useful, in order to maintain the efficiency of the pervious pavement over time.